Hepatic epithelioid haemangioendothelioma: difficult name, difficult diagnosis?. Issue 748 (February 1988) - Cobden, I.; Johri, S.; Terry, G.; Robinson, K. B.; Bennett, M. K.; Lendrum, R.
Abstract : Two patients with epithelioid haemangioendotheliomata of the liver are described. Both presented with abdominal pain and malaise, with hepatomegaly and a variable degree of hepatocellular dysfunction. Diagnosis was delayed in both cases, each patient undergoing a protracted series of investigations including repeated liver biopsies. The major obstacles to early diagnosis were a lack of clinical awareness of the condition and difficulties in interpretation of the liver histology: the widespread sclerosis in the tumour tissue is easily mistaken for a post-necrotic or cirrhotic process. The key to the diagnosis is the demonstration of cells containing Factor-VIII-related antigen confirming the endothelial origin of the tumour. One patient died within three months of presentation and the other after 18 months. The tumour may, therefore, be more aggressive than earlier reports seem to suggest. It seems likely that the tumour is being under-diagnosed and although no specific therapy has been shown to be of value, a greater awareness of the condition, resulting in a more prompt diagnosis, should save patients from undergoing unnecessary investigation.